Sistema de qualificação múltiplo para corrida utilizando sensor ultrassônico E ESP32 - Silva, João Vitor Silveira da (Brasil, 2024)
The proposed work aims to enhance the tracking system used in the qualifying races for amateur motor racing competitions held at the Manaus Kartodrome Olympic Arena. The need to revise the current system arises from its limitation to time only one racer at a time, which not only hampers the efficiency of the process but also prevents the removal of previous racers and complicates the control of the number of participants, their categories, and the various championship heats. To meet these needs, the project proposes an approach that integrates IoT (Internet of Things) devices with low energy consumption, with a special focus on ESP32 microcontrollers, and ultrasonic sensors, which are used to accurately measure the distance between cars on the track. This integration is complemented by a web application developed using modern technologies such as NodeJS and Angular. The new architecture of the system allows for the registration of championships, cars, racers, and categories, providing event organizers with total control over the championship. Additionally, the times recorded by IoT devices are promptly displayed on an intuitive user interface, facilitating subsequent data analysis.